Efforts on Geological Conservation to Watuadeg-Basalt Pillow Lavas at West Sumber, Berbah District, Sleman Regency, Yogyakarta Special Region-Indonesia - Mohamad Faizal; Rydo Faisal Arisandy; Ariel l Afrandi Tatawu; Shandi Hargian Wijaksono; Frando Ryan Alansa; Muhammad Nur Arifin; Sri Mulyaningsih (UIR PRESS, 2018)
Site of Berbah pillow lavas is an important geological heritage that is currently as one of the main tourism destination area located in Yogyakarta Special Region, Indonesia. It has a unique appearence of pillow structures with diameters of 0.5-1.0 m and the flow length of 2-5m. This site is used to visited by students and earth researchers becouse of its unique geological history. This study was approached with geotourism and geoconservation points of view. The research method uses qualitatively field geological observations. Data analysis was carried out by assessing the feasibility study of the geological conditions that had been produced in relation to the development of educational toursm. In its condition, this site suffered damage to the development impacts in the surrounding area and was once an object of agate mining so that its condition was increasingly not maintained. In order to maintain this site and become a protected geological site, there must be seriousness of various parties in an effort to map the geological conditions of the pillow lava complex, an important role that geologists have to inform and disseminate to all stakeholders and local residents to be able to independently manage the potential of geotourism. In addition, it also needs the commitment of the local government in protecting the pillow lava object and fighting for it to become a protected geological reserve.